AACAP expert on young people and guns: Treating and consulting. Issue 4 (25th March 2018) - Unknown
Abstract : Louis J. Kraus, M.D., is an expert in forensic psychiatry; he is an associate professor and section chair at Rush University Medical Center, and chair of the American Academy of Child & Adolescent Psychiatry's (AACAP's) Assembly of Regional Organizations. We spoke to him last month after the Feb. 14 shooting by a former student at Marjory Stoneman Douglas High School in Parkland, Florida, in which 17 people, mostly students, were killed.